A Bibliometric Analysis of Inclusive Education in Indonesia: Achievement and its Relations to General Education - Dianastiti, Firstya Evi; Suwandi, Sarwiji; Setiawan, Budhi (PLD UIN Sunan Kalijaga, 2024)
This bibliometric analysis study used Vosviewer application as a data processor. Data sources in the form of research articles were collected from Dimension.ai using the keyword